PROSPECTS OF USING INFRARED THERMOGRAPHY IN THE DIFFERENTIAL DIAGNOSIS OF BRONCHOPULMONARY PATHOLOGICAL CONDITIONS - Zabolotnyi, Dmytro I.; Zabrodska, Liudmyla V.; Dunaievskyi, Vadym I.; Kotovskyi, Vitaliy Y.; Tymofieiev, Volodymyr I.; Nazarchuk, Svitlana S. (Eastern Ukrainian Medical Journal, 2026)
Introduction. The search for new non-invasive diagnostic methods for detecting pathological changes in the bronchopulmonary system is a pressing issue in modern medical diagnostics, gaining even greater significance during the COVID-19 pandemic. Existing clinical and morphological diagnostic methods for the differential diagnosis of viral and viral-bacterial pneumonia often require significant time for data acquisition and processing. There is substantial scientific and practical interest in developing a differential diagnostic method using remote infrared thermography to identify patients with viral and viral-bacterial pneumonia and to study the characteristics of thermographic visualization of the pulmonary system under various pathological conditions. This method allows for a rapid and non-invasive identification of the nature of the pathology. Purpose of the study. To obtain thermal images of the posterior projection of the lungs in individuals with a history of bronchopulmonary pathology; to analyze the obtained thermographic images and oscillographic temperature distributions in the areas of interest; and, based on this information, to develop a method for the differential diagnosis of pathological states of the bronchopulmonary system. Materials and methods. The study utilized a domestically developed thermograph with a temperature sensitivity of 0.07 °C developed by the V.E. Lashkaryov Institute of Semiconductor Physics of the NAS of Ukraine, featuring a cooled focal plane array and the ThermoVisio base test software, as well as a FLIR SYSTEM ThermaCAM E300 thermograph. Observations and control of thermal fields were conducted in the 3 ÷ 5 µm and 8 ÷ 14 µm ranges. Results. Thermographic images and oscillographic temperature profiles of the posterior lung projection were obtained for various bronchopulmonary diseases. The analysis and processing of these images and distributions revealed significant differences in thermographic visualizations and oscillograms depending on the pathogenic agent. It was demonstrated that infrared thermography enables differential diagnosis of respiratory tract lesions. In conjunction with other clinical and laboratory methods, thermography simplifies the diagnostic search and treatment strategy. Conclusions. A method for the differential diagnosis of bronchopulmonary pathological states using remote infrared thermography has been developed. The implementation of this thermal imaging method allows for the investigation of temperature pattern distributions in the posterior lung projection. It was found that thermographic visualization of the lung projection in patients with COVID-19-associated pneumonia lacks the clear inflammatory focus areas characteristic of viral-bacterial pneumonias of other etiologies. Infrared thermography is a promising method for detecting bronchopulmonary diseases caused by various pathogens.